Akurasi Pulse Oximetry dalam menentukan hipoksemia - Effendy, Christantie; Basuki, Endro; Sianipar, Osman; Suryono, Bambang (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2009)
Please refer to the file